1974
DOI: 10.1063/1.1682549
|View full text |Cite
|
Sign up to set email alerts
|

Zeeman nuclear quadrupole resonance line shapes in powders (I = 3/2)

Abstract: Theoretical absorption line shapes are presented for Zeeman perturbed nuclear quadrupole resonance transitions (I = 3/2) in polycrystalline materials for the case in which the rf field is parallel to the Zeeman field. For a nuclear spin of 3/2, the pure quadrupole transition frequency νQ(1+η2/3)1/2 is insufficient to independently determine either νQ, the strength of the quadrupole interaction, or η, the asymmetry in the electric field gradient tensor. Application of a magnetic field removes the degeneracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…For I = 3/2, there is a method devised (Morino & Toyama, 1961) which allows the evaluation of the two values from a powder Zeeman experiment. The shape of Zeeman NQR lines in crystal powder is considered by Brooker & Creel (1974). However, literature shows that only in a few cases are the correct data found.…”
Section: Methodsmentioning
confidence: 99%
“…For I = 3/2, there is a method devised (Morino & Toyama, 1961) which allows the evaluation of the two values from a powder Zeeman experiment. The shape of Zeeman NQR lines in crystal powder is considered by Brooker & Creel (1974). However, literature shows that only in a few cases are the correct data found.…”
Section: Methodsmentioning
confidence: 99%
“…Brooker and Creel [5] have shown that for / = 3/2 the features or peaks in the line-shape occur at the following critical points H//x, H//y and H//z, V0 » YH/atr . where .x, y, z refer to the 1, 2, 3 axes of the principal axes system.…”
Section: The Zeeman Line Shapes In Polycrystalline Materialsmentioning
confidence: 99%
“…Brooker and Creel [5] and Darville, Gerard and Calende [6] have independent ly given a full analysis of the problem where the applied magnetic field and the r.f. field were parallel.…”
Section: General Considerationsmentioning
confidence: 99%
“…The Zeeman effect on NQR for powder specimens (PZNQR) has been studied theoretically and/or experimentally [1][2][3][4][5][6][7][8][9]. In the case of nuclear spin 3/2, an asymmetry parameter of electric field gradient (77) at the nuclear site cannot be determined only from the NQR frequency, so that the Zeeman NQR method using single crystal (SZNQR) has usually been adopted.…”
Section: Introductionmentioning
confidence: 99%